Distinctive roles of land-use efficiency in sustainable development goals: An investigation of trade-offs and synergies in China. (1st January 2023) - Song, Wen; Cao, Shisong; Du, Mingyi; Lu, Linlin
Abstract: Achieving the 17 sustainable development goals (SDGs) proposed by the United Nations 2030 Agenda for Sustainable Development is an intercommunicated mission worldwide. It is primarily known that increasing urban areas and populations can considerably influence numerous SDGs. However, the interaction mechanism between urban expansion (UE), urban population dynamics (UPD), land-use efficiency, and SDGs, until now, has not been fully understood. The present study employed remotely sensed data of population and land covers to analyze spatiotemporal variations in land consumption rate (LCR), population growth rate (PGR) and the ratio of LCR to PGR (LCRPGR) of 31 provinces in China from 1995 to 2015. Moreover, we investigated the relations between land-use efficiency and SDG practice using the Spearman coefficient and explored how economic zones alter the consequence of LCR, PGR, and LCRPGR on SDG implementations. The results show that nine SDGs had synergies with LCRPGR, exceeding the total number of synergy relationships yielded by LCR and PGR, indicating that LCRPGR that considers both LCR and PGR exerts more impacts on SDG implementations compared with the single perspective concerning LCR or PGR. The synergies and trade-offs of LCRPGR were more evident in undeveloped economic zones, while few influences of LCRPGR on SDGs were observed in developing economic zones. It suggests that improving land-use efficiencies to facilitate SDG implementation is essential in undeveloped economic settings. The study provides a better understanding of SDG practice in land-use efficiency for developing countries, i.e., China, and guides the regulations of urban expansion and population growth. Graphical abstract: Image 1 Highlights: The impact of land-use efficiency on SDGs 1–17 were systematically analyzed. LCRPGR exerted more effect on SDG implementations compared with LCR and PGR. How economic zones change the impact of LCRPGR on SDGs was investigated. Synergies and trade-offs of LCRPGR on SDGs were more evident in undeveloped economic zones.